2016
DOI: 10.1136/archdischild-2016-310898
|View full text |Cite
|
Sign up to set email alerts
|

Influence of own mother's milk on bronchopulmonary dysplasia and costs

Abstract: Background Human milk from the infant’s mother (own mother’s milk; OMM) feedings reduces the risk of several morbidities in very low birthweight (VLBW) infants, but limited data exist regarding its impact on bronchopulmonary dysplasia (BPD). Objective To prospectively study the impact of OMM received in the neonatal intensive care unit (NICU) on the risk of BPD and associated costs. Design/methods A 5-year prospective cohort study of the impact of OMM dose on growth, morbidity and NICU costs in VLBW infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
62
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 40 publications
3
62
0
7
Order By: Relevance
“…Data from the German Neonatal Network, however, showed that exclusively formula-fed infants had 2.6-times the risk of developing BPD in multivariate analysis than exclusively breastmilk-fed infants 56. In another cohort study, multivariable analysis showed a 9.5% reduction in the odds of BPD for every 10% increase in expressed breastmilk 57. These data further encourage the use of breastmilk instead of formula in ELGANs.…”
Section: Introductionmentioning
confidence: 92%
“…Data from the German Neonatal Network, however, showed that exclusively formula-fed infants had 2.6-times the risk of developing BPD in multivariate analysis than exclusively breastmilk-fed infants 56. In another cohort study, multivariable analysis showed a 9.5% reduction in the odds of BPD for every 10% increase in expressed breastmilk 57. These data further encourage the use of breastmilk instead of formula in ELGANs.…”
Section: Introductionmentioning
confidence: 92%
“…6,7,21 The prospectively collected data included maternal age, highest education level (completed less than high school, high school, less than 4-year college, 4-year college or graduate degree), self-stated race/ethnicity (non-Hispanic black [black], non-Hispanic white [white], Hispanic, other [six Asian, one Native American]), marital status (dichotomous), and Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) eligibility (dichotomous). 23 Since Asian mothers comprised a very small proportion of the cohort and had similar socioeconomic characteristics and breastfeeding rates 24 to the white mothers in the cohort, Asian and white mothers were combined in analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The exclusion criteria have been described previously 6,7,21 ; HM feeding was not a prerequisite for study participation. As per standard practice, all mothers received the same lactation care by employed NICU-specific breastfeeding peer counselors, all of whom are former NICU parents and represent the racial/ ethnic composition of the patients cared for at RUMC.…”
Section: Methodsmentioning
confidence: 99%
“…Patel and colleagues4 report the results of a prospective observational cohort study evaluating the impact of own mother’s milk on bronchopulmonary dysplasia (BPD) and NICU costs in 254 very low birthweight (VLBW) infants cared for in a single center between 2009 and 2012. Given that BPD is both a common and costly morbidity in premature infants, the primary aim of the study was to evaluate whether there is a dose–dependent relationship between mother’s own milk ingested in the NICU and BPD and associated healthcare costs.…”
mentioning
confidence: 99%